Development and Validation of the Maternal and Partner Sex During Pregnancy Scales. Issue 8 (16th November 2016) - Jawed-Wessel, Sofia; Herbenick, Debby; Schick, Vanessa; Fortenberry, J. Dennis; Cattelona, Georg'Ann; Reece, Michael
Abstract : Little is known about current attitudes in the United States toward having sex during pregnancy. It is possible that pregnant women and their sexual partners hold beliefs and have feelings during this time that might lead to sexual and relational distress. Two new scales, Maternal Sex During Pregnancy and Partner Sex During Pregnancy, were developed and administered to 112 newly pregnant couples. The scales demonstrated strong reliability and validity. Attitudes and beliefs varied across the sample, but the scores did not significantly differ between partners. These scales allow clinicians to support healthy sexuality during pregnancy by understanding sources of anxiety and possible misconceptions.